Alteration in T lymphocyte subpopulations in inflammatory bowel disease. - Victorino, R M (1980)
Peripheral blood mononuclear cells from thirty-one patients with inflammatory bowel disease (ulcerative colitis and Crohn's disease) were analysed for the proportions and absolute numbers of total T cells, and for the T cell subpopulations carrying Fc receptors for either IgM (Tmu cells) or IgG (T gamma cells). Twenty-six control subjects were studied simultaneously. Total T cell numbers were normal in patients with inflammatory bowel disease but there was a marked reduction in the proportion and absolute numbers of Tmu cells in patients, whether their disease was active or in remission. T gamma cells were normal. Simultaneous assessment of lymphocyte response to mitogens in vitro was performed in a group of patients. Responses to phytohaemagglutinin, concanavalin A and pokeweed mitogen were decreased and a positive correlation was found between the number of circulating Tmu cells and the responses to mitogens in vitro. These studies demonstrate that despite the presence of normal numbers of total T cells in inflammatory bowel disease, there is a marked imbalance in T cell subpopulations that correlates with mitogen responsiveness. This imbalance provides a possible cellular basis for the defect in cell-mediated immunity seen in these patients.